Decentralization of Foreign Cooperation: Case Study of Sister Province Cooperation Between West Java, Indonesia And South Australia [Desentralisasi Kerja Sama Luar Negeri: Studi Kasus Kerja Sama Antara Pemerintah Provinsi Jawa Barat, Indonesia Dan Austra] - Andriani Florencia Dharmajaya; Anggara Raharyo (Jurnal Politica, 2019)
Cooperation between cities and states/provinces has gained its attention in contemporary global affairs. Most scholars refer to it as para-diplomacy, which can be defined as cooperation between sub-national actors for the benefit or the interest of the national governments. This research focuses on the practice of para-diplomacy between West Java Province of Indonesia and South Australia. It aims to explain the progress of the sister province cooperation out of the renewal of its agreement in 2015 and their progress of cooperation until 2017. This research utilizes annual reports of the cooperation from both sides of the parties to identify the practices and progress of the cooperation. From the analysis, cooperation in agriculture, fisheries, and tourism, including culture and education are still in the developing progress. Nevertheless, several sectors have shown an improvement on the West Java’s side.AbstrakKerja sama antar Pemerintah Kota dan Pemerintah Provinsi telah menjadi salah satu perhatian di studi Hubungan Internasional. Mayoritas peneliti menamakan hal ini sebagai aktivitas paradiplomasi yang berarti kerja sama yang dilakukan oleh aktor sub-nasional untuk mendapatkan manfaat atau mencapai kepentingan nasional. Penelitian ini berfokus pada praktek paradiplomasi antara Pemerintah Provinsi Jawa Barat dengan Australia Selatan. Penelitian ini bertujuan untuk menjelaskan perkembangan dari kerja sama provinsi yang telah dilaksanakan dari pembaharuan perjanjian kerja sama pada tahun 2015 hingga tahun 2017. Penelitian ini menggunakan laporan tahunan dari kedua belah pihak sebagai sumber utama. Dari analisis ini, kerja sama dalam bidang pertanian, perikanan, dan pariwisata serta kebudayaan dan pendidikan masih dalam tahap perkembangan awal. Walaupun, beberapa sektor telah menunjukkan perkembangan yang baik, terutama bagi Jawa Barat.